2008
DOI: 10.1038/eye.2008.234
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Gram-positive bacterial keratitis associated with epidemic keratoconjunctivitis in neonates and infants

Abstract: Objectives To report the clinical characteristics of bacterial keratitis associated with epidemic keratoconjunctivitis (EKC) and to evaluate the risk factors for bacterial keratitis development in eyes with EKC. Methods After 108 patients diagnosed as EKC were retrospectively reviewed, clinical characteristics and incidence of bacterial keratitis-associated EKC were described. To analyse the effect of steroid use and the methicillin-resistant Staphylococcus aureus (MRSA) colonization in conjunctiva on developi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…[28,[34][35][36] mentioned earlier, there is a large variation of culture-positive rate in the studies of healthy eyes (47-95%) as well as diseased eyes. [6,14,28,34,35,37] In this study, the positive culture rate in patients with PBSCT-related dry eye and in nonhematopoietic transplantation-related dry eye patients were even lower than that of healthy eyes in the previous study. The difference in the culture methodology and different culture locations may explain the variation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…[28,[34][35][36] mentioned earlier, there is a large variation of culture-positive rate in the studies of healthy eyes (47-95%) as well as diseased eyes. [6,14,28,34,35,37] In this study, the positive culture rate in patients with PBSCT-related dry eye and in nonhematopoietic transplantation-related dry eye patients were even lower than that of healthy eyes in the previous study. The difference in the culture methodology and different culture locations may explain the variation.…”
Section: Discussionmentioning
confidence: 95%
“…Among diabetic patients, a significantly higher frequency of positive culture rate is detected in those with diabetic retinopathy than in those without. [14] The study by Miller and Ellis revealed a positive correlation between increasing doses of prednisone and the number of bacterial organisms in the patients' conjunctiva. [16] Therefore, the of ocular surface flora.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 5 These bacteria are also common causes of ocular infections including keratitis and conjunctivitis. 6 9 Streptococcus pneumoniae is reported to be the most common bacterial pathogen of acute conjunctivitis in children. 7 Staphylococcus aureus , including methicillin-resistant S. aureus (MRSA), along with Pseudomonas aeruginosa , are increasingly isolated in elderly patients with conjunctivitis.…”
mentioning
confidence: 99%
“…Conjunctivitis owing to MRSA was reported as the first case in an epidemic that eventually involved 14 neonates in an NICU including multiple invasive infections and two deaths [677]. MRSA has also caused dacrocystitis [678] and keratitis [679] in neonates.…”
Section: Conjunctivitis and Other Eye Infectionsmentioning
confidence: 99%